Analytical Examination of Reinforced Concrete with Hybrid Fibres Exterior Beam Column Joint. Issue 3 (December 2020) - Maruthachalam, D; Shyamala, G; Boobalan, S C; Sandhya Rani, B; Muthukrishnan, V
Abstract: This research paper pacts with the analytical examination of synthetic fibres (Polypropylene and Recycled polyethylene terephthalate RPET) and steel fibres in reinforced exterior beam column joint by using ANSYS. Based on IS 10262-2009, M40 grade of concrete was prepared along by volume fractions up to 0.5% of synthetic and steel fibre. 9 number of exterior beam column joint with various proportions of hybrid fibre incorporated reinforced concrete specimens were tested by means of monotonic loading. Their experimental results exhibited that reinforced concrete exterior beam column joint specimens with hybrid fibre specimens achieved superior performance along with high ductility, high strength and less crack patterns. The main aim of this research paper was based on the experimental input, analytical examination by ANSYS was carried out and related with the experimental results found. The comparison showed that both the experimental and numerical results similar.